1994
DOI: 10.1113/jphysiol.1994.sp020232
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic responses of substantia gelatinosa neurones to dorsal column stimulation in rat spinal cord in vitro.

Abstract: 1. To study the mechanism of dorsal column stimulation-induced depression of nociceptive transmission in the spinal cord, synaptic responses evoked in dorsal horn neurones by dorsal column and dorsal root stimulations were examined in a horizontal spinal cord slice of the adult rat. Intracellular recordings were made from substantia gelatinosa (SG) neurones. 2. All SG neurones examined received monosynaptic inputs and/or polysynaptic inputs from both dorsal column and dorsal root. Ad fibres were probably respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 38 publications
6
33
0
Order By: Relevance
“…Analysis of the IPSPs in the SG at the single cell level, however, has been hampered mainly due to the difficulty of obtaining stable intracellular recordings in in vivo experiments. We have developed an in vitro slice preparation which retains an attached dorsal root, cut from the adult rat spinal cord (Yoshimura & Jessell, 1989, 1990Yoshimura & Nishi, 1993;Baba et al 1994). In the present study, we report that the stimulation of primary afferent Ad fibres evokes two different types of IPSPs (short and long IPSPs) in substantia gelatinosa neurones and that the short and long IPSPs are mediated by strychnine-and bicuculline-sensitive receptors, respectively.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Analysis of the IPSPs in the SG at the single cell level, however, has been hampered mainly due to the difficulty of obtaining stable intracellular recordings in in vivo experiments. We have developed an in vitro slice preparation which retains an attached dorsal root, cut from the adult rat spinal cord (Yoshimura & Jessell, 1989, 1990Yoshimura & Nishi, 1993;Baba et al 1994). In the present study, we report that the stimulation of primary afferent Ad fibres evokes two different types of IPSPs (short and long IPSPs) in substantia gelatinosa neurones and that the short and long IPSPs are mediated by strychnine-and bicuculline-sensitive receptors, respectively.…”
mentioning
confidence: 82%
“…The methods used for obtaining slice preparations of adult rat spinal cord were similar to those described elsewhere (Yoshimura & Nishi, 1993;Baba et al 1994). Briefly, male Sprague-Dawley rats (6-12 weeks old) were anaesthetized with urethane (1'2 g kg-', i.p.)…”
Section: Methods Preparation Of the Spinal Cord Slicementioning
confidence: 99%
See 2 more Smart Citations
“…Fine myelinated Aδ and unmyelinated C primary afferent fibers, many of which innervate nociceptors, tend to terminate preferentially on the neurons of the superficial dorsal horn, particularly the SG neurons (21 -29). Intracellular recording studies of the SG neurons have also revealed that the stimulation of primary afferent evokes monosynaptic fast excitatory postsynaptic potentials (EPSPs) and inhibitory postsynaptic potentials (IPSPs) in the majority of SG neurons (30,31). In addition, in vivo patch-clamp recording studies have shown that the majority of SG neurons are excited by noxious stimuli (21,22).…”
Section: Introductionmentioning
confidence: 99%